Pengembangan Media Pembelajaran E-Learning Berbasis Schoology - Supratman, Edi; Purwaningtias, Fitri (Jurnal Informatika: Jurnal Pengembangan IT, 2018)
Learning with the E-learning method is learning by using technology because online e-learning uses computer networks to provide information and communication. Where with the use of e-learning can occur changes in learning activities between teachers and students and students can learn wherever and whenever. SUMSEL N HIGH SCHOOL (Sampoerna Academy) Palembang has a vision that is international level and has the hope to become an example for other national schools by implementing international standards and has a mission to make students global in mind. In the SUMSEL High School in the learning process still using conventional learning methods through face-to-face in class, the provision of subject matter is carried out only in class and also if the teacher is not entered, the subject material is not obtained by students. So that this research was carried out by utilizing information and communication technology in changing learning activities namely the use of school-based elearning. While this research is research and development research refers to the development model Analyze, Design, Develop, Implement, Evaluation (ADDIE). School-based Elearning has features similar to Facebook and schoology also combines social networks and LMS (Learning Management System). So that with schoology-based e-learning can get information about the subject matter that is given by the teacher easily even though the teacher is unable to attend the class because through schoology the teacher can attend student attendance, and between the teacher and students can interact socially while learning.